Gender Equality in Islamic Education: Insights from Indonesia’s Muslim Heroines - Masitoh, Siti; Lailatul Qodriyah, Nisa; Widia Astuti, Renny; Haryanti, Erni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Gender equality in Islamic education is becoming increasingly significant in the context of the Industrial Revolution 5.0. This study examines how values exemplified by Indonesia’s Muslim heroines, like R.A. Kartini, Dewi Sartika, and Nyai Ahmad Dahlan, can inspire innovative approaches to promoting and supporting women’s roles in education. Through a qualitative library study, this research examines Islamic teachings alongside the contributions of these heroines, highlighting core values of justice and social responsibility. Its argues that the Islamic educational principles championed by these female role models can significantly contribute to advancing women's leadership capabilities, enhancing their digital literacy, and expanding their access to education. This study addresses challenges such as limited access to higher education, societal expectations, and cultural norms. It also highlights specific initiatives, including leadership programs, digital learning platforms, and family education. The findings suggest that the teachings and values of Indonesia’s Muslim Heroines have the potential to help overcome these barriers, it is possible to create supportive environments that empower women to take on leadership roles and actively participate in education.